2021
DOI: 10.1002/ejlt.202100019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steric Structure on the Mechanism of Antioxidant Activity of Alkyl Gallates in Soybean Oil Triacylglycerols—A Kinetic Approach

Abstract: From an interfacial phenomena standpoint, the effect of the alkyl chain length is evaluated on the mechanism of antioxidant activity of gallic acid ester derivatives (methyl, propyl, octyl, dodecyl, and stearyl gallates) in bulk phase oil. A combinational kinetic model is used to estimate the oxidation kinetic parameters, such as induction period, the maximum concentration of lipid hydroperoxides, and critical reverse micelle concentration. These kinetic parameters are estimated much better with the combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Our previous studies showed that the optimal concentration of alkyl gallates with maximum efficiency in oil is 1.2 mM (Delfanian, Sahari, Barzegar, & Ahmadi, 2021). Hence, this concentration was used in oil, which is equal to 0.84 mM in the emulsion.…”
Section: Emulsion Preparation and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies showed that the optimal concentration of alkyl gallates with maximum efficiency in oil is 1.2 mM (Delfanian, Sahari, Barzegar, & Ahmadi, 2021). Hence, this concentration was used in oil, which is equal to 0.84 mM in the emulsion.…”
Section: Emulsion Preparation and Samplingmentioning
confidence: 99%
“…Selection of an efficient antioxidant is an essential challenge in emulsion-based foods because its efficiency depends on innate potency as a chelating agent or radical scavenger, concentration in the interfacial region, and interaction with other reactants and components (Delfanian, Sahari, Barzegar, & Ahmadi Gavlighi, 2021). The interfacial concentration of antioxidant molecules depends on their distribution between the aqueous, interfacial, and oil phases, which depends on the physicochemical attributes of the antioxidant (e.g., hydrophobicity, and degree of ionization) and environmental conditions (nature of the oil, oil-water ratio, and surfactant concentration, etc.)…”
Section: Introductionmentioning
confidence: 99%